THE ROLE OF LANGUAGE PHILOSOPHY IN ENGLISH LEARNING IN THE INDEPENDENT CURRICULUM - Nurmiati; Artati Alwiah; Nur Afifah; St. Nurhayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the role of philosophy of language in supporting the implementation of the Independent Curriculum. The main focus of the study is to determine how theories of philosophy of language can strengthen the planning and implementation of learning, thereby improving student competence and achievement. The research methodology uses a qualitative approach with a literature review design. Data were obtained through searching relevant journal articles, books, and research reports. Data analysis was conducted using content analysis techniques to identify patterns, gaps, and the contribution of philosophy of language in the development of English language learning according to the Independent Curriculum. The results show that philosophy of language plays a significant role in improving the quality of English language learning in the Independent Curriculum. Pragmatics emphasizes the importance of contextual communication, constructivism builds active student involvement, speech acts strengthen the social function of language, hermeneutics deepens text understanding, and structuralism strengthens the foundation of the language system. The integration of these theories has been proven to support the improvement of communicative skills, critical thinking, and student academic achievement.